Experience of chronic electrical stimulation application for pain management in thoracic outlet syndrome - Vitaliy Tsymbaliuk; Ihor Tretyak; Boris Luzan; Hao Jiang (Ukrainian Neurosurgical Journal, 2016)
Introduction. Pain is the only common symptom in thoracic outlet syndrome. Ensuring a stable analgesic effect remains challenging today.The aim of the study was to evaluate the efficacy of pain relief in thoracic outlet syndrome by continuous electrical stimulation, application.Materials and methods. Results of surgical treatment of 21 patients with thoracic outlet syndrome were analysed. The main clinical symptom in those patients was pain. The intensity of pain was evaluated by a standard visual analog scale. All patients underwent standard surgical techniques with the classic anterior approach including neurolysis of the brachial plexus structures, angiolysis of subclavian vessels, scalenotomy of the supraclavicular area, resection of the extra cervical rib (if necessary) and additional implantation of electrical stimulating system (ESS) “NeySi-3M” (SPE “WEL”, Ukraine) for continuous electrical stimulation of the brachial plexus in the postoperative period.Results. Regression of pain was observed in 95.2% of patients.Conclusions. Chronic electrical stimulation of the brachial plexus allows achieving a stable and safe analgesic effect in thoracic outlet syndrome.